Business Impact of COVID-19 Pandemic on Pharmacy Shops of Dharan-18: A Sample Survey - Regmi, Sumitra Devi (Dristikon: A Multidisciplinary Journal, 2020)
The present study aims to describe the effect of the COVID-19 pandemic and the government imposed lockdown on the business activities of pharmacy shop owners (as small business operators) in the locality of Dharan-18. A sample survey was carried out in 32 participants using a self-designed and self-administered questionnaire comprising participants ‘demographic details and 14 question items concerning the impact of the pandemic and lockdown on their businesses. All the participants responded. The results show that all the pharmacy operators were adversely affected by the pandemic and the imposed lockdown. Most of the businesses temporarily suspended their operations while some stopped operating. The essential supplies and access to goods and services as well as financial access have been severely hindered; however, no remarkable price hike has been observed. The expectations of the participants about changes in near future lack consistencies. The participants have expressed lack of confidence in carrying out business in the forthcoming days. In conclusion, the COVID-19 pandemic and the government-imposed lockdown has affected almost all of the pharmacy operators in the locality of Dharan-18.